2014
DOI: 10.1039/c4dt01143k
|View full text |Cite
|
Sign up to set email alerts
|

Hemilability of P(X)N-type ligands (X = O, N–H): rollover cyclometalation and benzene C–H activation from (P(X)N)PtMe2complexes

Abstract: The thermolyses of ((tBu)P(O)N)PtMe2 (, (tBu)P(O)N = (di-tert-butylphosphinito)pyridine) and ((tBu)P(N-H)N)PtMe2 (, (tBu)P(N-H)N = (di-tert-butylphosphino)-2-aminopyridine) in benzene-d6 were investigated. With ((tBu)P(O)N)PtMe2, the product of a rollover cyclometalation of the pyridyl ring was observed in 80% yield along with formation of CH4. In contrast, thermolysis of ((tBu)P(N-H)N)PtMe2 resulted in competing rollover cyclometalation and intermolecular benzene C-H activation with production of a mixture of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…Remarkably, the complex with the pyrimidine ligand [PdCl(Ph 2 PNHpym)(PPh 3 )]Cl, generated in situ by reaction between the neutral complex and PPh 3 , achieves practically complete conversion and chemoselectivity and 97 % regioselectivity in the branched ester (entry 3), as it happens with its pyridine analog [23]. This comparable result with the pyridine ligand indicates that the reported rollover cyclometalation of the aromatic ring in related complexes [24], which is prevented in the pyrimidine ligand, does not have a contribution to the noteworthy performance of the catalysts [PdCl(P,X) (PPh 3 In summary, these catalytic experiments confirm that [PdCl(Ph 2 PNHpy)(PPh 3 )]Cl and its pyrimidine analog here described are particularly appropriate catalysts for an efficient and selective methoxycarbonylation of styrene.…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…Remarkably, the complex with the pyrimidine ligand [PdCl(Ph 2 PNHpym)(PPh 3 )]Cl, generated in situ by reaction between the neutral complex and PPh 3 , achieves practically complete conversion and chemoselectivity and 97 % regioselectivity in the branched ester (entry 3), as it happens with its pyridine analog [23]. This comparable result with the pyridine ligand indicates that the reported rollover cyclometalation of the aromatic ring in related complexes [24], which is prevented in the pyrimidine ligand, does not have a contribution to the noteworthy performance of the catalysts [PdCl(P,X) (PPh 3 In summary, these catalytic experiments confirm that [PdCl(Ph 2 PNHpy)(PPh 3 )]Cl and its pyrimidine analog here described are particularly appropriate catalysts for an efficient and selective methoxycarbonylation of styrene.…”
Section: Resultssupporting
confidence: 69%
“…A recent report revealed that the complex [Pt( t Bu 2-PNHpy)Me 2 ] undergoes partial rollover cyclometalation of the pyridyl ring concurrent with methane evolution (scheme 1) [24]. Because of the similarity of this ligand to Ph 2 PNHpy, it is not possible to exclude a priori that a metalation process also takes place during the methoxycarbonylation reaction.…”
Section: Introductionmentioning
confidence: 98%
“…To address the structural properties affected by changes in the chelate size, five-membered PN chelates ( L 7 )­PtMe 2 ( 11 ; L 7 = t Bu 2 PCH 2 CH 2 NMe 2 ) and ( L 8 )­PtMe 2 [ 12 ; L 8 = (2-pyridyl)­CH 2 P t Bu 2 ] were prepared by the addition of the appropriate ligand to [Pt 2 Me 4 (μ-SMe 2 ) 2 ]. The X-ray structure of 11 was obtained and is presented for comparison with four-membered chelates in Scheme c, while the structure of 12 was reported previously by Goldberg and co-workers . The data for the four-membered chelate complexes confirm their monomeric nature and show distorted square-planar geometries (τ 4 = 0.13–0.15) because of the small ligand bite angles of close to 70° [ 7 , 71.4(2)°; 9 , 70.0(2)°; 10 , 68.90(7)°].…”
mentioning
confidence: 72%
“…The X-ray structure of 11 was obtained and is presented for comparison with four-membered chelates in Scheme 3c, while the structure of 12 was reported previously by Goldberg and co-workers. 14 The data for the fourmembered chelate complexes confirm their monomeric nature and show distorted square-planar geometries (τ 4 = 0.13−0.15) 15 because of the small ligand bite angles of close to 70° [7, 71.4(2)°; 9, 70.0(2)°; 10, 68.90(7)°]. These angles are significantly smaller than those in related diphosphinomethane complexes (∼74°).…”
mentioning
confidence: 99%
“…Goldberg et al. reported that thermolysis of dimethyl‐platinum complex supported by phosphinito‐pyridine and phosphino‐aminopyridine ligands in C 6 D 6 , gives cleanly the expected rollover complexes, respectively (Scheme , c) …”
Section: Introductionmentioning
confidence: 99%